2005
DOI: 10.1590/s0100-41582005000100009
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting density of airborne Gibberella zeae inoculum

Abstract: Fusarium head blight (FHB) is a disease of increasing concern in the production of wheat (Triticum aestivum). This work studied some of the factors affecting the density of airborne Gibberella zeae inoculum. Spore samplers were placed at the edge of a field in order to observe spore deposition over a period of 45 days and nights in September and October, the period that coincides with wheat flowering. Gibberella zeae colonies were counted for each period and values transformed to relative density. A stepwise r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 13 publications
1
16
0
1
Order By: Relevance
“…The effect of moisture coming from the soil on inoculum production was previously mentioned by Xu (27), who reported that ascospore production is prevented when the soil moisture is Ͻ30% and is at its maximum when soil moisture is Ͼ80%. The dynamics of ascospore discharge were similar in the two conditions (stalks on a moist substrate versus stalks on a grass lawn exposed to rain), suggesting that ascospore discharge is not affected by stalk moisture but is mainly driven by rain and atmospheric humidity (18,46,47,48).…”
Section: Discussionmentioning
confidence: 90%
“…The effect of moisture coming from the soil on inoculum production was previously mentioned by Xu (27), who reported that ascospore production is prevented when the soil moisture is Ͻ30% and is at its maximum when soil moisture is Ͼ80%. The dynamics of ascospore discharge were similar in the two conditions (stalks on a moist substrate versus stalks on a grass lawn exposed to rain), suggesting that ascospore discharge is not affected by stalk moisture but is mainly driven by rain and atmospheric humidity (18,46,47,48).…”
Section: Discussionmentioning
confidence: 90%
“…The model assumes inoculum as a non-limiting factor. In southern Brazil, most wheat is cropped under a no-till system, and airborne inoculum seems to be always present when the environment is highly suitable for infections (rainfall and RH>80%), which corresponds well with peaks of spore detection (Reis, 1990;Panisson et al, 2002;Del Ponte et al, 2005). Other locations may be more dependent on exogenous inoculum sources, and infections may be absent or low if inoculum is not present or at very low levels.…”
Section: Discussionmentioning
confidence: 96%
“…Models for predicting the daily relative density of a GZ spore cloud were developed by the observation on the night-and day-time deposition of G. zeae airborne inoculum in Passo Fundo, Brazil (Del Ponte et al, 2005). A linear equation was adjusted to the relative density of colony forming units that was observed during the night-time to estimate the relative density of a spore cloud [3].…”
Section: Inoculum Factormentioning
confidence: 99%
“…A sobrevivência saprofítica do patógeno em diversos hospedeiros, como espécies de plantas cultivadas, nativas e invasoras (REIS & CASA, 2004), assim como a facilidade de dispersão dos ascosporos, transportados a longa distância pelo vento, faz com que a giberela não seja controlada eficientemente pela rotação de culturas (ZAMBOLIM et al, 2000;REIS & CASA, 2005). A grande disponibilidade de inóculo no ar (PANISSONN et al, 2002b;DEL PONTE et al, 2005), durante o período de floração (antese), associada a períodos de molhamento contínuo (REIS & BLUM, 2004), ocorrentes com freqüência na Região Sul do Brasil, tem levado a danos significativos na cultura no trigo (PANISSON et al, 2003;CASA et al, 2004 a,b).…”
Section: Introductionunclassified